An Overview of Fingerprint Patterns among Students of Gandaki Medical College, Pokhara, Nepal - Hirachan, N; Shrestha, R; Koju, S; Limbu, D (Journal of Gandaki Medical College-Nepal, 2019)
Introduction: Fingerprint system of positive identification is based on the principle that the arrangement and distribution of fingerprint remains constant and persists throughout life and that the patterns of no two hands resemble each other.Methods: A cross sectional study was carried out among 250 students (125 male and 125 female students), aged 17 - 40 years of age, of Gandaki Medical College, Pokhara, Nepal from 15 March to 13 April, 2017 A.D. The fingertip patterns of both hands were collected and identified with the aid of a magnifying glass and documented as: Loops, Whorls, Arches and Composite type. The data were enrolled in SPSS version 16 and analyzed accordingly.Results: There was a preponderance of loop pattern (52.6%) followed by whorls (39.4%), arches (7.3%) and composite (0.6%). Whorls (41.7%) were more common in males compared to females (37.1%) and females had more arches (9.6%) compared to that of the male counterparts (5.04%). There was no significant difference in fingerprint patterns among male and female students.Conclusion: The predominance of loops amongst other fingerprint patterns along with no significant gender differences in fingerprint patterns can be considered as a valuable research finding in the field of forensic science.